Literature Synthesis on Determinants of Sustainable Competitive Advantage in Furniture MSMEs: The Role of Green Innovation, Environmental Performance, and Market Orientation - Excella Cleodora Lamahayu; Febrian Dwi Wijaya; Anna Triwijayati; Catharina Aprilia Hellyani (EBISMAN eBisnis Manajemen, 2026)
This literature review synthesizes findings from fifteen peer‑reviewed studies published between 2020 and 2026 to examine the determinants of sustainable competitive advantage in the furniture industry. The analysis reveals that green innovation, environmental performance, and market orientation interact as core drivers of competitiveness, supported by theoretical perspectives including the Resource‑Based View, Natural Resource‑Based View, Institutional Theory, Circular Economy, and Strategic Management frameworks. The review highlights how internal capabilities, regulatory compliance, and responsiveness to consumer preferences collectively shape the ability of micro, small, and medium enterprises to adapt to sustainability demands in global markets. Evidence shows that eco‑innovation practices, waste recovery strategies, and clustering models enhance efficiency and legitimacy, while indicators of green growth and brand performance provide practical tools for evaluating sustainability outcomes. The synthesis underscores that competitive advantage in this sector is not determined by isolated variables but by systemic integration across resources, operations, and market dynamics. This study contributes theoretically by consolidating fragmented insights into a coherent conceptual model and practically by offering guidance for enterprises and policymakers to foster green transformation. The findings emphasize the urgency of aligning industrial practices with ecological integrity and suggest that future research should examine cross‑country variations, longitudinal impacts, and the integration of digital technologies with sustainability strategies to strengthen the resilience of furniture enterprises in the global economy.